2018
DOI: 10.1101/336784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nociceptor translational profiling reveals the RagA-mTORC1 network as a critical generator of neuropathic pain

Abstract: One Sentence SummaryCell-specific sequencing of translating mRNAs elucidates signaling pathology that can be targeted to reverse neuropathic pain Abstract (100-125 words)Pain sensing neurons, nociceptors, are key drivers of neuropathic pain. We used translating ribosome affinity purification (TRAP) to comprehensively characterize upand down-regulated mRNA translation in Scn10a-positive nociceptors in chemotherapy-induced neuropathic pain. We provide evidence that an underlying mechanism driving these changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…7-2, available at https://doi.org/10.1523/JNEUROSCI. 2663-18.2019.f7-2), a finding that is consistent with observations in DRG Nav1.8-expressing neurons (Megat et al, 2019).…”
Section: Nav1supporting
confidence: 90%
See 3 more Smart Citations
“…7-2, available at https://doi.org/10.1523/JNEUROSCI. 2663-18.2019.f7-2), a finding that is consistent with observations in DRG Nav1.8-expressing neurons (Megat et al, 2019).…”
Section: Nav1supporting
confidence: 90%
“…This approach generates Nav1.8-TRAP neurons in both the DRG and TG. While the specificity of our approach was recently shown in the DRG (Megat et al, 2019), we characterized expression of the transgene in the TG (Fig. 1A).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…BDNF is a key molecule mediating pain plasticity ( Obata and Noguchi, 2006 ) and identification of MNK/eIF4E signaling as a central regulator of Bdnf translation has important therapeutic implications ( Moy et al, 2018a ). Cell-type specific translational profiling of nociceptors [using translating ribosome affinity purification (TRAP) approach] ( Heiman et al, 2014 ) in a mouse model of chemotherapy-induced neuropathic pain revealed that MNK-eIF4E signaling controls translation of RagA mRNA, a key regulator of mTORC1 ( Megat et al, 2018 ). This finding suggests crosstalk between ERK/MNK/eIF4E and mTORC1 signaling pathways in promoting pain hypersensitivity in chemotherapy-induced neuropathies.…”
Section: Eif4e In Regulation Of Peripheral Nociceptive Plasticitymentioning
confidence: 99%